2000
DOI: 10.1209/epl/i2000-00384-1
|View full text |Cite
|
Sign up to set email alerts
|

Micellization of amphiphilic diblock copolymers: Corona shape and mean-field to scaling crossover

Abstract: The aggregation behaviour of six amphiphilic poly(ethylene-propylene)-blockpolyethylene oxide (PEP-PEO) copolymers in water was investigated with the aim to study systematically the influence of a growing soluble block on the structural properties of the micelle. The polymers were prepared such that they differ in the PEO content over a large range of molecular weights, while the PEP size was kept constant. The micelles were characterized by small-angle neutron scattering (SANS) involving contrast variation ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
95
2

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(107 citation statements)
references
References 22 publications
(13 reference statements)
10
95
2
Order By: Relevance
“…6b) while the density profile falls off smoothly at the polymer/solvent interface for the power law model. In similar studies on micellar systems the density profile in the corona region was crucial to fit SANS data from poly(ethylene -propylene)-block-polyethylene oxide (PEP -PEO) copolymer micelles in water [11]. A continuously decreasing density profile following a hyperbolic function shape for the micelle interface showed a better fit than a homogeneous density profile for the shell (for high PEO content polymers) which is consistent with the results presented here.…”
Section: Iðqþsupporting
confidence: 84%
“…6b) while the density profile falls off smoothly at the polymer/solvent interface for the power law model. In similar studies on micellar systems the density profile in the corona region was crucial to fit SANS data from poly(ethylene -propylene)-block-polyethylene oxide (PEP -PEO) copolymer micelles in water [11]. A continuously decreasing density profile following a hyperbolic function shape for the micelle interface showed a better fit than a homogeneous density profile for the shell (for high PEO content polymers) which is consistent with the results presented here.…”
Section: Iðqþsupporting
confidence: 84%
“…Within a so-called ''blob'', a spherical volume with radius , the dendrons have to be described as a selfavoiding random walk and excluded-volume interaction has to be considered. 36 Following a similar ansatz of Dozier et al 37 for highfunctionality stars, which has also, in a different modification, been successfully applied to polymeric micelles, 38 we split the dendrimer form factor into the sum of two terms…”
Section: Sphere With Fuzzy Shell and Internal Density Fluctuationsmentioning
confidence: 99%
“…This study 44 (as well as ref 42) has the merit that data close to the cmc could be taken, and it was shown that the micelle formation near the cmc is spread out over about a full decade in concentration. Finally, we mention the work of Willner et al, 45 who studied the structure of micelles varying the length of the block in the corona over a wide range and showed that the starlike model is applicable only for N B . N A , while the theory of Nagarajan and Ganesh 27 works better for not so large N B .…”
Section: Concluding Remarks and Comparison With Experimentsmentioning
confidence: 99%
“…9,11,14,18,[23][24][25][26][27] In fact, this point has already been made by several authors, and systemspecific predictions 27 have been made for several blockcopolymer-solvent systems and also carried out a comparison with experiment. 37 Further experimental studies where these theoretical predictions are tested can be found in refs [38][39][40][41][42][43][44][45]. Such studies are also clearly difficult to perform, since the critical micelle concentration (φ cmc ) seems to decrease almost exponentially with N, at least according to the model calculations.…”
Section: Introductionmentioning
confidence: 99%